Conformational and substitution effects on the donor and reducing strength of Tin(II) porphyrinogens - Ruppert, Heiko; Meister, Arne; Janßen, Paul; Greb, Lutz (Chemistry - a European journal, 2024)
Meso-octaalkylcalix[4]pyrrolates are a class of redox-active porphyrinogen ligands. They have been well established in d- and f-block chemistry for over three decades but have only recently been introduced as ligands for p-block elements. Here, we present a study on the influence of meso-substituents on the redox chemistry of calix[4]pyrrolato stannate(II) dianions [2R]2− (R=Me, Et). Expansion of the normal-mode structural decomposition (NSD) method, well known for porphyrin chemistry, provides insights into the ligand conformation of a calix[4]pyrrolato p-block complex. Combined with the results of spectroscopic donor scaling, electrochemical studies, and quantum mechanical bond analysis tools, subtle but significant substitution and conformational effects on the electronic structure are revealed. Exploiting this knowledge rationalizes the role of this class of tin(II) dianions to act as potent reducing agents, but can also be expanded for other central elements. Photoexcitation boosts this reactivity further, allowing for the reduction of even challenging chlorobenzene.